Private bank money vs central bank money: A historical lesson for CBDC introduction - Anna Grodecka-Messi; Xin Zhang (Sveriges Riksbank, 2023)
Central banks have been considering the introduction of central bank digital currencies (CBDCs). The theoretical literature indicates that this may influence private banks' lending activity and their profitability with implications for financial stability. To provide empirical evidence on this debate, we study the effects of the arrival of a new central-bank issued currency on commercial banks in a historical setup. We use the opening of the Bank of Canada in 1935 as a natural experiment to provide evidence that banks mostly affected by the currency competition experienced lower profitability but did not decrease their lending compared to unaffected peers
Keywords: E42; E5; G21; G28; N22; 330; Money and Banking; Central Bank Digital Currencies; Central Banks; Bank Profitability; Bank Lending; Bank of Canada; Banknote Monopoly